Odontogenesis-associated phosphoprotein (ODAPH) Promotes Ameloblast adhesion and alkaline phosphatase (ALP) expression via LAMC2/ ITGB6/TGF-β1 signaling pathway. - Mingyue Li; Jie Zhang; Shuang Xiao; Xinyang Liu; Shuai Song; Xiaoyuan Ye; Ruonan Bi; Yuguang Gao; Li Zhang (PLoS ONE, 2025)
Recessive hypomineralized amelogenesis imperfecta has been linked to mutations in Odontogenesis-Associated Phosphoprotein (ODAPH). Consistent with human phenotypes, Odaph-null mice exhibit defective enamel mineralization with ameloblast detachment from the enamel surface. To elucidate the mechanistic basis, we investigated ODAPH's role in ameloblast adhesion and mineralization using ameloblast-lineage cells (ALCs). Key findings demonstrate that Odaph overexpression enhanced Lamininγ2 (LAMC2)/Integrinβ6(ITGB6)/TGF-β1/Alkaline Phosphatase(ALP) pathway activity. Notably, co-immunoprecipitation confirmed interactions between ODAPH and LAMC2. Functional analyses revealed that ITGB6 activates the TGF-β1/ALP signaling cascade. Inhibition of integrin (CWHM-12) abrogates ODAPH-mediated TGF-β1/ALP induction. TGF-β1 positively regulates both LAMC2/ITGB6 expression and ALP activity. These results establish that ODAPH orchestrates ameloblast adhesion and mineralization via the LAMC2/ITGB6/TGF-β1/ALP signaling axis.